Analisis Perbandingan Simpangan Lateral dan Volume Material Antara Variasi Balok Grid Sejajar dan Diagonal pada Bangunan Beton Bentang Lebar (Mengacu pada Peraturan American Concrete Institute) - Angga Satriadi; Hanafiah .; Imron Fikri Astira (Jurnal Teknik Sipil dan Lingkungan, 2013)
In the concrete’s buildings with large spans , the using of the ordinary structure system will create  the dimensions of the beam , column , and plate are large so that the building be disproportionate . Therefore, the waffle slab structure system was developed . Waffle slab is crossed beam system that is used to increase the stiffness of the plate , so that the smaller the deflection occurs , thus dimensional of structural elements can be minimized and eventually become less material usage . Waffle slab has many types , including the type of parallel waffle slab and diagonal waffle slab. This research aims to determine which system is more economical and rigid between the two types of those . This research uses 1 ordinary building model as a standard , 5 parallel waffle slab’s building and 5 diagonal waffle slab’s building with Lx and Ly spans is 10 m , height of each floor is 4 m , and given the same loads in accordance with the regulations of the American Society of Civil Engineers ( ASCE ) . There are 5 combinations of crossed beams who start of division 1 Lx and 1 Ly to division 5 Lx and 5 Ly for each waffle slab building model  . This research was supported by the program Extended Three Dimensional Analysis of Building Systems ( ETABS ) and refers to the regulation American Concrete Institute ( ACI ) . The results showed that the parallel waffle slab 1-1 has the best level of the material’s efficiency , amounting to 29.38 % , while the diagonal waffle slab 4-4 even more wasteful 38.78 % compared to the ordinary building’s structure .The  diagonal waffle slab 5-5 is the most rigid system , It’s stiffness increased by 40.41 % , while the parallel waffle slab 4-4 56.19 % more flexible than the ordinary building’s structure, but the drift is still into the limits of the allowable story drift. Keywords : Waffle Slab, ETABS , ACI , Drift , Efficiency